2022
DOI: 10.1016/j.cmi.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Muyocopron laterale: invasive human infection of a plant pathogen in an immunocompromised host

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Jiang et al reported the first instance of Muyocopron laterale infection in plants in China [ 11 ], while Lye et al reported the first case of infection in an immunocompromised patient [ 12 ]. Unfortunately, the patient's outcome was poor despite limb amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported the first instance of Muyocopron laterale infection in plants in China [ 11 ], while Lye et al reported the first case of infection in an immunocompromised patient [ 12 ]. Unfortunately, the patient's outcome was poor despite limb amputation.…”
Section: Discussionmentioning
confidence: 99%